2014
DOI: 10.1002/2013ef000174
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and analysis of air quality in Islamabad, Pakistan

Abstract: Ambient air quality of Islamabad, Pakistan, reveals that annual average mass concentration of particulate matter (PM 2.5 ) (∼45 to ∼95 μg m −3 ) and nitric oxide (NO) (∼41 to ∼120 μg m −3 ) exceeds the Pakistan's National Environmental Quality Standards (NEQS). The annual ozone (O 3 ) concentration is within the permissible limits; however, some of the hourly concentration exceeds the NEQS mostly during the summer months. Correlation studies suggest that carbon monoxide (CO) has a significant (p-value ≤ 0.01) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In addition to in situ monitoring, intensive field campaigns have been conducted to address specific science issues such as the export of pollutants from South Asia to the adjacent oceanic (e.g., Moorthy et al, ; Ramanathan et al, ) and Himalayan (Moorthy et al, ; Sarkar et al, ) regions, and the role of aerosols in enhanced/prolonged fog events in the Indo‐Gangetic Plain (IGP) (Nair et al, ; Ram & Sarin, ; Tripathi et al, ). A few measurements of surface ozone and related gases with complete seasonal cycle have also been reported from Pakistan (Rasheed et al, ), Nepal (Pudasainee et al, ; Putero et al, ), and Bangladesh (Sikder et al, ).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition to in situ monitoring, intensive field campaigns have been conducted to address specific science issues such as the export of pollutants from South Asia to the adjacent oceanic (e.g., Moorthy et al, ; Ramanathan et al, ) and Himalayan (Moorthy et al, ; Sarkar et al, ) regions, and the role of aerosols in enhanced/prolonged fog events in the Indo‐Gangetic Plain (IGP) (Nair et al, ; Ram & Sarin, ; Tripathi et al, ). A few measurements of surface ozone and related gases with complete seasonal cycle have also been reported from Pakistan (Rasheed et al, ), Nepal (Pudasainee et al, ; Putero et al, ), and Bangladesh (Sikder et al, ).…”
Section: Introductionmentioning
confidence: 96%
“…In addition to in situ monitoring, intensive field campaigns have been conducted to address specific science issues aerosols in enhanced/prolonged fog events in the Indo-Gangetic Plain (IGP) (Nair et al, 2007;Ram & Sarin, 2010;Tripathi et al, 2006). A few measurements of surface ozone and related gases with complete seasonal cycle have also been reported from Pakistan (Rasheed et al, 2014), Nepal (Pudasainee et al, 2006;Putero et al, 2015), and Bangladesh (Sikder et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Ambient air quality monitoring of Islamabad, Pakistan showed annual average concentrations of PM 2.5 and nitric oxide as 45-95 μgm −3 and 41-120 μgm −3 , respectively, which are higher than Pakistan's National Environmental Quality Standards [11]. The highest levels of measured TSP, PM 10 , SO 2 , NO x , and ozone have been observed in Lahore [12].…”
mentioning
confidence: 84%
“…Although Pakistan's oil and coal consumption is much lower than that in Xinjiang and India, Pakistan is home to some of the most polluted cities in the world (WHO, 2019) due to the lack of emission controls and air quality standards (Colbeck et al, 2010;Sánchez-Triana et al, 2014). These cities include Peshawar, Rawalpindi, Lahore, Faisalabad, and Pakistan's capital, Islamabad (Rasheed et al, 2014;WHO, 2019;Shi et al, 2018), all located in northern Pakistan, from which air parcels have been shown to strongly influence the Guliya site throughout the year. Air parcels from Xinjiang and India, on the other hand, only reach Guliya during sum-mer (Fig.…”
Section: Fossil Fuel Combustionmentioning
confidence: 99%